Pemikiran Muhammad Bin Abdul Wahhab dalam Kitab Tauhid: Pemurnian Ibadah Kepada Allah - Ismanur Hasanah (GHAITSA : Islamic Education Journal, 2025)
This paper explores the thoughts of Shaykh Muhammad bin Abdul Wahhab At-Tamimi on the concept of tawhid as a way to purify worship to Allah SWT which is manifested in the Book of Tawhid. The analysis of this thought includes At-Tamimi's view of tawhid which is divided into three main categories, namely tawhid rububiyah, tawhid uluhiyah, and tawhid asma' wa sifat. In addition, to understand the spread of At-Tamimi's thought in academia, the paper further incorporates bibliometric analysis by mapping the development and pattern of research on the focus of the Book of Tawhid. The bibliometric analysis results in the mapping of research trends, authorship networks, and scholarly contributions on At-Tamimi's thought in the context of Islamic theology.